Coffee Houses Culture in Erbil: A Review - Herdn Ibrahim Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Coffee has been known to the world since the 12th century, and it has begun to serve a drink in a special place known as coffeehouse since the 14th century. At first, it was only for drinking coffee, then it has become a place for chatting and sharing problems with other people. Coffee shops are regarded as a significant place from the 16th century until now. Coffee shops are serving under different names in Erbi, but the coffee shops are the modern name. Furthermore, they have significant effects on the human progress, by performing many functions such as changing information, news. To sum up, coffee shops provide an opportunity for people to discuss political, cultural, social and economic subjects